Effect of Combination Miding Fern (Stenochlaena palustris) and Iron Tablet to Pregnant Women at Sintang Regency - Nurmala Sari; Eny Sunarsih; Rohuna; Aspia Lamana (Science Midwifery, 2022)
Hemoglobin is one of the components of red blood cells to bind oxygen and then deliver oxygen to all body tissue cells. Lack of hemoglobin will cause anemia, which can increase the risk of morbidity in mother and baby. The purpose of this study was to analyze the effect of the combination of miding fern and iron tablets on hemoglobin levels in pregnant women in the Working Area of ​​the Nanga Ketungau Public Health Center, Sintang Regency. This research was a quantitative study. The population were all pregnant women in the 1st to 3rd trimester in the Working Area of the Nanga Ketungau Public Health Center, Sintang Regency, totaling 298 pregnant women. In this study used consecutive sampling technique. The total sample were 33 respondents. Results: The median value before the intervention was 11.20 g/dl and after the intervention it was 13.10 g/dl. The p-value was 0.000 where p<0.05. Conclusion: There is an effect of the combination of miding fern (Stenochlaena palustris) and iron tablets on the increase in hemoglobin levels in pregnant women in the Working Area of ​​the Nanga Ketungau Public Health Center, Sintang Regency.